2009
DOI: 10.1051/radiopro/20095098
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the dose assessment tools on the basis of dispersion of the99Tc in the Nordic Seas and the Arctic Ocean

Abstract: Abstract. Compartment models are widely used for the evaluation of radiological consequences to man and biota in the marine environment over large spatial and long temporal scales. The model developed at the Norwegian Radiation Protection Authority (NRPA) is based on a compartment modelling approach that includes terms describing dispersion of radionuclides into oceanic space with time (non-instantaneous mixing in oceanic space). In this paper the latest modification of the NRPA model will be presented. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Simulations over several months may be carried out for spatial scales of some hundred km. For even longer-term assessments (years to decades and thousand km), box models should be used (Lepicard et al, 2004;Iosjpe et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Simulations over several months may be carried out for spatial scales of some hundred km. For even longer-term assessments (years to decades and thousand km), box models should be used (Lepicard et al, 2004;Iosjpe et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This fact highlights that developing operational models for emergency management and decision-making support (which is one of the main application of numerical modelling) in these dynamic environments should be based on the reliable operational oceanographic model calibrated for this area. The same time it is important to note that the models that were integrated into the decision support system RODOS within EC project PREPARE -THREETOX and POSEIDON, that were refined within the project on the basis of the experience of the UVEV and Iosjpe et al (2009) model development, demonstrated during the described intercomparison study "the state of the art" level of the marine dispersion modelling.…”
Section: Discussionmentioning
confidence: 99%
“…Box models are well suited for assessments of radionuclide dispersion involving large spatial and temporal scales (thousand kilometres; years to decades). Some recent examples of box models are POSEIDON-R (Lepicard et al, 2004;Maderich et al, 2014a,b;Bezhenar et al, 2016), models developed in NRPA (Iosjpe et al, 2002(Iosjpe et al, , 2009 and others (Sánchez-Cabeza et al, 2002;Håkanson, 2005;Smith and Simmonds, 2009; for instance).…”
Section: Box Modelsmentioning
confidence: 99%